Effect of epicanthoplasty on the descent of the eyebrow - Yong-Il Shin; Kyoung-Jin Kang; Jae-Ran Hong; Montri Khammoonta; Phoebe Kar Wai Lam; Sang-Yoon Lee (Journal of Cosmetic Medicine)
Background: Epicanthoplasty is an additional surgical technique for blepharoplasty, often performed in conjunction with ptosis correction surgery or eyelid crease surgery, rather than as a standalone procedure. Numerous studies have reported on the functional improvement after upper eyelid and ptosis correction surgeries, which can lead to eyebrow descent. However, no studies have been conducted on the effects of epicanthoplasty alone. Objective: We observed changes in eyebrow position and patient satisfaction immediately after epicanthoplasty in patients undergoing both procedures, before proceeding with ptosis correction surgery. Methods: Among 15 patients who underwent epicanthoplasty and ptosis correction surgery at a Seoul cosmetic surgery clinic between October 2018 and March 2019, nine patients (eight females and one male) were included. Six patients were excluded due to photographic errors. Changes in eyebrow descent, palpebral fissure morphology from preoperative and postoperative photographs, and patient satisfaction were assessed. Results: After epicanthoplasty, the average descent of the eyebrow at the medial, central, and lateral positions was 1.78±1.2, 1.5±1.0, and 0.89±1.2 mm in 18 numbers of eyelids, respectively. Although no statistically significant reductions were observed in specific areas, morphological changes indicated a greater decrease in the central and medial regions. The vertical length of the palpebral fissure measured 10.9±1.6 mm preoperatively and 11.09±1.9 mm postoperatively in 18 numbers of eyelids, showing no statistically significant increase. Patient satisfaction regarding comfort while opening the eyes was 3.78±0.67 when lying down but decreased to 2.33±0.87 after changing to a sitting position. Conclusion: Epicanthoplasty causes eyebrow descent and morphological changes, reduces discomfort while opening the eyes, and ultimately increases patient satisfaction.